A short and modular synthesis of bulky and electron-rich N-phosphinomethyl-functionalised N-heterocyclic carbene complexes - Brill, Marcel; Kühnel, Erik; Scriban, Corina; Rominger, Frank; Hofmann, Peter (Dalton transactions, 2013)
Bulky and electron-rich N-phosphinomethyl-substituted N-heterocyclic carbene transition metal complexes have been prepared in a short and efficient protocol. The modular synthesis allows one to convert borane-protected phosphino-functionalized imidazolium salts into their corresponding metal chelate complexes in a one-pot procedure.